An autopsy case of poisoning with ethanol and psychotropic drugs - Kinoshita, Hiroshi; Nishiguchi, Minori; Kasuda, Shogo; Ouchi, Harumi; Minami, Takako; Matsui, Kiyoshi; Yamamura, Takehiko; Motomura, Hiroyuki; Ohtsu, Nao; Yoshida, Shie; Adachi, Nobuyuki; Aoki, Yasuo; et al. (Soudni lekarstvi, 2008)
A case of fatal poisoning involving ethanol with psychotropic drugs is presented. Quantitative toxicological analysis showed that the concentrations of ethanol, amoxapine and phenobarbital in the femoral blood were 2.86 mg/ml, 0.41 microg/ml and 6.80 microg/ml, respectively. We concluded that the cause of death was due to the combination use of ethanol, amoxapine and phenobarbital.
Keywords: Psychotropic Drugs; psychotropní léky; Female; Adult; dospělí; Phenobarbital; ethanol; Ethanol; ženské pohlaví; Humans; lidé; amoxapin; fenobarbital; Amoxapine